Acute Rhinosinusitis in Children: a Place of Nasal Decongestants in the Treatment of the disease - H.V. Beketova (Zaslavsky O.Yu., 2016)
The article presents current data on acute rhinosinusitis, its essence, classification, etiology, pathogenesis, treatment approaches in children. It is emphasized that the key to successful treatment of this disease is the impact on all parts of pathogenesis. Given the leading etiopathogenetic links of acute rhinosinusitis, its comprehensive treatment requires prescribing of preparations with anti-infection, anti-inflammatory, secretolytic and immune-stimulating action, as well as nasal decongestants - to eliminate the swelling of the nasal mucosa and to improve the quality of life of the patient. The detailed description of nasal decongestants is presented, the attention is paid to the next generation drug without preservatives - dosed nasal drops Nasivin® Sensitive.